Sistem Pembelajaran Multimedia dengan Teknologi Voice Recognition untuk Berkebutuhan Khusus - Nabila Ade Mutmaina; Tata Sutabri (JOURNAL SAINS STUDENT RESEARCH, 2025)
The purpose of this study is to develop a multimedia learning system that can assist children with special needs in learning through the use of voice processing technology. Children with special needs require different learning approaches, including the use of appropriate technology, methods, and media. Students with motor impairments or communication difficulties can interact verbally with the system through speech recognition technology, creating a more inclusive and interactive learning experience. The analysis results show that the system has the potential to increase students’ motivation to learn, enhance their understanding of the material, and improve accessibility for various types of learners, especially those with visual or auditory preferences. Therefore, the integration of speech recognition in multimedia learning systems can be an innovative solution for special education.